The Role of Islamic Economic Policy in Building Sustainable Welfare in the Era of Globalization - Dofiruddin; Wildhan Romdhoni; Ahmad Mahfud; Mashudi (Al-Abqori: Journal of Islamic Thought Studies, 2025)
This research aims to analyze the role of Islamic economic policy in building sustainable welfare in the era of globalization, focusing on policy instruments, challenges faced, and the potential for implementation in the global context. Islamic economic policies based on the values of justice, balance and sustainability have great potential to answer the challenges of socio-economic inequality and environmental degradation faced by the global community today. The research method used is a literature study, which includes reviewing literature from books, scientific articles, policy reports, and other related documents. The study identifies fundamental principles in Islamic economic policy, such as wealth redistribution through zakat and waqf, the prohibition of usury practices, and an inclusive approach to resource management. It also analyzes the implementation of Islamic economic policies in various countries to understand the successes and challenges in its implementation. The results show that Islamic economic policies can make a significant contribution to reducing socio-economic inequality and promoting sustainable prosperity. Instruments such as zakat and waqf have proven effective in supporting wealth redistribution, poverty alleviation, and improving people's access to basic services. In addition, the prohibition of usury and excessive speculation creates greater macroeconomic stability.